Gender problems in physical education. Historical and philosophical analysis - Oksana Marchenko; Lyudmila Tsykalo; Maria Brychuk; Natalia Symonenko (Kharkiv State Academy of Physical Culture, 2020)
Purpose: historico-philosophical analysis of gender issue in physical education and clarification of the meaningful characteristics of the category "gender" in the field of physical culture and sports. Material and methods: to achieve objectives of the research and for generalization the experience of those scientists who investigate educational problems of the gender approach, modern approaches to development and improvement of physical education we used such theoretical research methods as analysis, comparison, generalization, systematization, theoretical modeling. Results: the historical aspect of the beginning of the gender approach in physical education has certain differences and features that makes it a separate area of gender cognition according to which all pedagogical and socio-cultural aspects of youth physical education can have a gender dimension. The necessity of distinguishing and interpreting the gender approach as a definition in political, public and social environments is theoretically grounded, its significance for physical training and sports is indicated, and a new term is suggested for use in research, which allows characterizing it as an interdisciplinary and cross-sectoral definition, extrapolated, interconnected and corresponding to the development of physical education and sports in the countries of developed democracy. Conclusions: acording to the results which were obtained during the research and the theoretical and methodological papers of the gender problem the necessity and expediency of the development and introduction of the gender component in the physical education of modern schoolchildren as an essentially new and progressive direction of the axiological significance of physical culture is justified. The essential and substantive characteristics of the category "gender" in the field of physical culture and sports in the context of psychological and pedagogical research are given.